Switched - Hocking, Amanda (Trylle trilogy, 2012)
When Wendy Everly was six years old her mother was convinced she was a monster and tried to kill her, and eleven years later Wendy learns that her mother was right and that she is actually a changeling troll, who, at the age of seventeen, must be returned to her rightful home.